2022
DOI: 10.3389/fnut.2021.780567
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone App-Based Lifestyle Change Program for Prediabetes (D'LITE Study) in a Multiethnic Asian Population: A Randomized Controlled Trial

Abstract: IntroductionLandmark studies have established that lifestyle interventions focused on weight loss, diet modification and physical activity can prevent diabetes progression. However, the effectiveness of mobile health application among Asians with prediabetes remains largely unexamined. We aimed to assess whether a smartphone app-based lifestyle intervention program would lead to weight loss, normoglycemia and improved metabolic indices in a multiethnic Asian population with prediabetes.Research Design and Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…This systematic review was comprised of 19 studies with randomized trial designs [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] and 6 studies [ 55 , 56 , 57 , 58 , 59 , 60 ] with other types of trial designs (pragmatic trial and quasi-experimental). The features of the studies are detailed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review was comprised of 19 studies with randomized trial designs [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] and 6 studies [ 55 , 56 , 57 , 58 , 59 , 60 ] with other types of trial designs (pragmatic trial and quasi-experimental). The features of the studies are detailed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of thirteen studies [ 36 , 39 , 40 , 41 , 43 , 44 , 46 , 48 , 50 , 51 , 53 , 57 , 58 ] only used hbA1c as a diagnostic tool for prediabetes. Research conducted by Ramachandran [ 36 ] only used an oral glucose tolerance test (OGTT) as a diagnostic standard for prediabetes.…”
Section: Resultsmentioning
confidence: 99%
“…This prospective cohort study included prespecified subgroup analysis of all participants from the intervention arm of the D’LITE study (N=171) who were assigned the Nutritionist Buddy Diabetes (nBuddy Diabetes) app [ 11 , 12 ]. A full description of the D’LITE study and the intervention details for both diabetes and prediabetes groups have previously been published [ 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The primary Diabetes Lifestyle Intervention using Technology Empowerment (D’LITE) study has shown that both participants with prediabetes or diabetes achieved significant weight loss with a mean difference of −3.1 kg (95% CI −4.5 to −1.7; P <.001) and −2.4 kg (95% CI −3.5 to −1.3; P <.001) at 6 months, respectively, when compared with the control group [ 11 , 12 ]. The participants with prediabetes were 2.1 times likely to achieve normoglycemia (defined as HbA 1c <5.7%) than in the control group ( P <.018).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile health apps, designed to support and reinforce health behaviors or to reduce risk behaviors, are among the most commonly downloaded apps, since they offer a novel and effective way for health professionals to engage users in the promotion and adoption of new behaviors (11,12). Several mobile apps have been designed and developed specifically to increase physical activity levels (13,14), encourage weight loss through personal coaching (15,16), boost healthy food choices (17)(18)(19)(20), reduce sedentary behavior (21,22), assess and track dietary intake (23), assess psychological distress (e.g., anxiety, depression) (24), support smoke cessation (25), and reduce alcohol consumption (26). Moreover, mobile apps developed based on behavior change models and theories, including the integration of different behavior change strategies (e.g., cognitive behavioral therapy, goal setting, real time feedback), are considered the most effective in securing behavior change in their users (27,28).…”
Section: Introductionmentioning
confidence: 99%